Bemerkungen zum Kondolenzbrief P. Ross. Georg. III 2 - Shavrin, Jan (Hyperboreus, 2024)
The article focuses on the ﬁrst six lines of the letter written by a certain Serenus to his mother Antonia, in which he expresses his condolences on the death of a loved one (probably her father or husband). Based on the paleographical considerations made by previous scholars as well as other papyrus attestations I suggest a restoration of the name of the deceased, which was partly lost due to the damages suﬀered by the papyrus. Furthermore I provide possible parallels to the gnome used in the letter and also oﬀer an interpretation to the ﬁnal part of the passage discussed.